Advances in the Treatment of Anal Fistula: A Mini-Review of Recent Five-Year Clinical Studies - Ji, Lijiang; Zhang, Yang; Xu, Liang; Wei, Jun; Weng, Liping; Jiang, Jie (Frontiers in Surgery, 2021)
Anal fistula, with its complicated pathogenesis, has been considered as a clinical challenge for centuries. The risk of frequent recurrence and incontinence constitutes a considerable threat in the long-term treatment of anal fistula. In this work, we narratively reviewed the scientific literature of new techniques that have been used for anal fistula treatment over the recent 5 years, objectively evaluated the pros and cons of each technique on the basis of clinical outcomes, and tried to disclose the effective strategies for anal fistula treatment. Up to date, surgery is the main method used for treating anal fistula, but there is no simple technique that can completely heal complex anal fistula. In the course of surgery treatment, the healing outcome, and the protection of anal function should be weighed comprehensively. Among the innovative techniques that have emerged in recent years, combined techniques based on drainage Seton and LIFT-plug seem to be the relatively effective therapies, but their effectiveness requires more multi-center prospective randomized controlled trials with large sample size and long-term follow-up to be validated.